PENGARUH AUDIT TENURE, UKURAN KANTOR AKUNTAN PUBLIK, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study is to examine the influence of audit tenure, audit firm size, and audit rotation of audit quality. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2011 to 2013. Relationship and (or) influence between variable is described by using logistic regression analysis. The result showed that audit tenure has positive effect and no significant to the audit quality, audit rotation has positive effect and no significant to the audit quality. and audit firm size has negative effect and no significant to the audit quality.Keywords: Audit Tenure, Audit Firm Size, Audit Rotation, and Audit Quality